2022
DOI: 10.21577/0103-5053.20220003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Zika Virus Effects, Placenta Protection and Chemical Composition of Passiflora edulis Seeds Ethanolic Extract

Abstract: Various beneficial biological activities have been reported for passion fruit (Passiflora edulis), grown in tropical and subtropical regions. However, no study has yet demonstrated its action against the Zika virus (ZIKV) infection. The present study aimed to investigate the anti-ZIKV of the ethanolic passion fruit seed extract (PFSE), from which, liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis allowed to putatively annotate the occurrence of piceatannol, astringin, scirpusin A, scirpusin B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Extraction of extract yields is crucial in assessing the cost and benefits associated with potential nutraceutical development. Xavier and colleagues [7], when studying the ethanol extraction of the seeds of Passiflora edulis, obtained 4 times higher yields (7.9%). The degree of maturation of the fruit seems to be a factor that could influence the composition of the seeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of extract yields is crucial in assessing the cost and benefits associated with potential nutraceutical development. Xavier and colleagues [7], when studying the ethanol extraction of the seeds of Passiflora edulis, obtained 4 times higher yields (7.9%). The degree of maturation of the fruit seems to be a factor that could influence the composition of the seeds.…”
Section: Resultsmentioning
confidence: 99%
“…EPCIN did not alter cell viability up to a concentration of 50 μg/mL. Xavier and colleagues [7], when testing the cell viability (human placental HTR-8/SVneo) in the presence of the ethanol extract of Passiflora edulis seed, observed that there was no reduction in cell viability, even at the concentration used of 100 μg/ mL.…”
Section: Santos and Colleaguesmentioning
confidence: 94%
See 1 more Smart Citation
“…The cytotoxicity of PESE was investigated in the Vero E6 cell line and no decrease in cell viability was observed; however, at the highest concentration (100 µg/mL) there was an increase in cell viability, which according to the authors [36] may be related to a possible increase in mitochondrial proliferation or enzyme activity. The cell viability of human placental HTR-8/SVneo cells was also assessed in the presence of the extract, also with no reduction in cell viability at up to 100 µg/mL [36].…”
Section: Cytotoxicity Of the Seed Extract Of P Edulis (Pese) And Picmentioning
confidence: 95%
“…Our previous study identified six major phenolic compounds of PESE, including PIC, astringin, scirpusin A, scirpusin B, isookanin-7-O-glucoside, and naringenin-7-O-glucoside. Among them, PIC has emerged as a promising compound with important biological activities [36]. Hence, PIC was also investigated in this study, along with PESE.…”
Section: Antioxidant Activitymentioning
confidence: 99%